Effect of thymosin alpha-1 on subpopulations of Th1, Th2, Th17, and regulatory T cells (Tregs) in vitro - Yang,Xia (2012)
Thymosin alpha 1 (Tα1) has been shown to have beneficial effects on numerous immune system parameters, but little is known about the effects of Tα1 on patients with gastric carcinoma. The objective of this study was to determine the effect of Tα1 on subpopulations of Th1, Th2, Th17, and regulatory T cells (Tregs) in vitro, and to evaluate its efficacy as an immunoregulatory factor in patients with gastric carcinoma. We compared the effect of Tα1 on the frequency of CD4+ and CD8+ T cells, especially the CD4+CD25+Foxp3+ Tregs in peripheral blood mononuclear cells (PBMCs) from gastric carcinoma patients (N = 35) and healthy donors (N = 22). We also analyzed the changes in the proliferation of PBMCs in response to treatment with Tα1, and examined the production of Th1, Th2, and Th17 cytokines by PBMCs and tumor-infiltrating lymphocytes. The treatment of PBMCs from gastric cancer patients, with Tα1 (50 µg/mL) alone increased the percentage of CD4+CD25+Foxp3+ (suppressive antitumor-specific Tregs) from 1.68 ± 0.697 to 2.19 ± 0.795% (P < 0.05). Our results indicate that Tα1 increases the percentage of Tregs and IL-1β, TNF-α, and IL-6 in vitro.